2018
DOI: 10.3389/fmars.2018.00292
|View full text |Cite
|
Sign up to set email alerts
|

Mixotrophic Plankton in the Polar Seas: A Pan-Arctic Review

Abstract: Polar marine ecosystems are characterized by low water temperatures, sea ice cover, and extreme annual variation in solar irradiance and primary productivity. A review of the available information from the Arctic suggests that mixotrophy (i.e., the combination of photosynthetic and phagotrophic modes of nutrition in one cell) is wide spread among plankton. In the central Arctic Ocean (AO) in summer, mixotrophic flagellates such as Micromonas and Dinobryon can account for much of bacterivory. Planktonic ciliate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 111 publications
0
76
0
Order By: Relevance
“…Biases among records of CMs may also be particularly high owing to differential efforts at sampling CMs of different sizes. It is not common practice to identify to species level in plankton surveys, especially among the smaller flagellate cells that are coincidentally mixotrophic (Sanders & Gast, ; Stoecker & Lavrentyev, ). Incubation experiments have demonstrated ingestion of prey by these small CMs (< 20 µm), whereas taxonomic identification using traditional diagnostic approaches has been difficult owing to few distinctive features for these species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biases among records of CMs may also be particularly high owing to differential efforts at sampling CMs of different sizes. It is not common practice to identify to species level in plankton surveys, especially among the smaller flagellate cells that are coincidentally mixotrophic (Sanders & Gast, ; Stoecker & Lavrentyev, ). Incubation experiments have demonstrated ingestion of prey by these small CMs (< 20 µm), whereas taxonomic identification using traditional diagnostic approaches has been difficult owing to few distinctive features for these species.…”
Section: Discussionmentioning
confidence: 99%
“…Some co-occurring protist species (including competitors, prey and predators) are also known mixotrophs, although many are not often recorded because they are not themselves HAB species. Indeed, of the 80 CM species included within our analysis, 51 species were dinophytes, despite the importance of mixotrophy having been well recognized in other taxonomic groups (Gast et al, 2014;Stoecker & Lavrentyev, 2018;Unrein et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arctic phytoplankton communities experience extreme environmental conditions such as nutrient limitation, exposure to a long period of darkness (polar winter) and changes in light levels under the ice caused by the variation in snow coverage and ice thickness [15]. In such a highly variable context, it has been suggested that phago-mixotrophy (ability to combine photosynthesis and bacterivory) could be a common trophic strategy among Arctic protists [16]. At the scale of the global ocean, phago-mixotrophy is an important, but until recently underestimated, process for energy and nutrient transfer (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Phago-mixotrophy would be another advantageous trait that could contribute to the success of M. polaris in the Arctic. Under prolonged periods of darkness or low irradiance, phago-mixotrophs could survive, despite reduced or even null rates of photosynthesis, by supplementing their carbon requirements through phagocytosis [16, 35, 36]. Under oligotrophic conditions, phago-mixotrophy can also supply the cell with limiting nutrients [37].Micromonas has been previously hypothesized to be a phago-mixotroph in laboratory and field experiments [38][39][40][41].…”
mentioning
confidence: 99%